Design, implementation, and evaluation of faculty member evaluation process using electronic 360-degree method - Farin Tatari; Maryam Ebrahimi; Hamidreza Tadayon (BMC Medical Education)
Abstract Background The evaluation of faculty members plays a vital role in the successful implementation of educational programs and in improving the quality of university performance. Evaluation of faculty members by students is the most common type of evaluation, but it is not a complete mechanism for evaluating the role of faculty members. Since the evaluation of faculty members at the Neyshabur University of Medical Sciences was based on students, the researchers decided to conduct this study in order to designing, implementing and evaluating of faculty member evaluation process using electronic 360-degree method. Methods This study was a developmental research project conducted in 2022 and included three stages of design, implementation, and evaluation. Evaluation checklists for faculty members were developed through expert panel methods. A descriptive-analytical study with a cross-sectional approach was employed, utilizing researcher-made questionnaires to gauge satisfaction levels with the 360-degree evaluation method. Validity and reliability of the questionnaires were confirmed by experts. Data from 373 students and 48 faculty members were analyzed using SPSS software and statistical tests. Results Results indicated that evaluation sources and the weight of each source included students (40%), vice-chancellor (20%), head of department (30%), and peers (10%). Both faculty members and students expressed high satisfaction with the electronic 360-degree evaluation system. There was a significant difference in faculty members' satisfaction based on gender and age. Conclusions Given this satisfaction, university administrators are encouraged to adopt the 360-degree evaluation method to gain a comprehensive understanding of faculty performance.